2022
DOI: 10.1002/ab.22051
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Moral Outcomes of Relationship Aggression Scale: A measure of moral distress following intimate partner violence perpetration

Abstract: Research with military veterans has established that distress may arise in response to perpetrating violent behaviors that violate individuals' moral beliefs. To date, no studies have similarly examined morally‐related cognitive and emotional responses specifically among intimate partner violence (IPV) perpetrators. However, research on moral cognitions and emotions in response to IPV perpetration may inform understanding of the behavior and potential mechanisms for intervention. In the current series of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Spanish nursing students also described moral injury stemming from failure to help COVID-19 patients during the pandemic (Roca et al, 2021). In a sample of adults who reported engaging in intimate partner violence, moral distress was associated with higher levels of PTS, depression, and anxiety (Taverna & Marshall, 2023). Similarly, a study with undergraduate students found positive associations between PMIEs and mental health outcomes (Chaplo et al, 2019).…”
Section: Potentially Morally Injurious Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spanish nursing students also described moral injury stemming from failure to help COVID-19 patients during the pandemic (Roca et al, 2021). In a sample of adults who reported engaging in intimate partner violence, moral distress was associated with higher levels of PTS, depression, and anxiety (Taverna & Marshall, 2023). Similarly, a study with undergraduate students found positive associations between PMIEs and mental health outcomes (Chaplo et al, 2019).…”
Section: Potentially Morally Injurious Experiencesmentioning
confidence: 99%
“…Research suggests that PMIEs may be a risk factor for alcohol use; increased exposure to PMIEs was associated with increased alcohol outcomes among military members (Battles et al, 2018; Braitman et al, 2018; Currier et al, 2018). Additionally, college students are an understudied population in the context of PMIEs as only two studies to date quantitatively examine undergraduate samples (Chaplo et al, 2019; Taverna & Marshall, 2023). Civilians may experience PMIEs to a different degree than military samples, as war and conflict yield more PMIEs than the average civilian’s daily activities.…”
Section: Potentially Morally Injurious Experiencesmentioning
confidence: 99%